فاعلية برنامج الألعاب في الوسط المائي على تحسين الانتقال والتركيز عند الأطفال المصابين بالفرط الحركي - طوابية, إبراهيم; مزورة, امير فيصل (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
تهدف الدراسة إلى تنمية وتحسين التركيز و الانتباه لدى المصابين بفرط النشاط الحركي من خلال برنامج علاجي مائي ، الغرض من الدراسة هو فاعلية برنامج علاجي مائي في تحسين قدرات التركيز و الانتباه والمهارات الاجتماعيةلدى مصابين بالفرط الحركي ، العينة 8 أطفال مصابين باضطراب الفرط الحركي أخذت من المركز التأهيلي للألعاب المائية بمسبح معهد التربية البدنية والرياضية-مستغانم وقد تم اختيارها قصديا ، واستخدام المنهج التجريبي ملائم لطبيعة البحث و من أهم الاستنتاجات التي توصلنا إليها أن البرنامج العلاجي المائي قد أثر إيجابيا علىتحسين قدرات التركيز و الانتباه لديهم ولهذا نوصي باستخدام مثل هذه البرامج العلاجية في الدراسات لتعميمها مستقبلاً على أطفال الفرط الحركي في المراكز البيداغوجية و اتباع مبدأ التدرج من السهل إلى الصعب ومن البسيط إلى المعقد حيث أن هذه الطريقة تستجيب لي متطلبات المهارية لهذه الفئة مما يجعلها تحظى بإقبال كبير لها ، ضرورة اهتمام بفئة أطفال فرط النشاط الحركي من خلال تحسين ظروف ووسائل تكوينية لممارسة الأنشطة الرياضية(المسابح، المراكز البيداغوجية، ملابس السباحة، أدوات مساعدة في السباحة)، اجراء بحوث على عينات من الجنسين ومراحل عمرية أخرى من فئة فرط النشاط الحركي . // // // // The study aims to develop and improve concentration and attention in people with hyperactivity through a hydrotherapeutic program, the purpose of the study is the effectiveness of a hydrotherapeutic program in improving the abilities of concentration, attention and social skills in people with hyperkinesis, the sample is 8 children with hyperkinetic disorder taken from the rehabilitation center for water games in the swimming pool of the Institute of Physical Education and Sports - Mostaganem has been chosen intentionally, and the use of the experimental approach is appropriate to the nature of the research and one of the most important conclusions that we reached To it that the hydrotherapeutic program has positively affected the improvement of their concentration and attention abilities and for this we recommend the use of such therapeutic programs in studies to circulate them in the future to children hyperkinetic in pedagogical centers and follow the principle of gradation from easy to difficult and from simple to complex as this method responds to the requirements of the skill of this category, which makes it very popular for it, the need to pay attention to the category of hyperactivity children by improving conditions and formative means For sports activities (swimming pools, pedagogical centers, swimwear, swimming aids),Conducting research on samples of both sexes and other age stages of the hyperactivity category.
LAPA-2024-7
Keywords: برنامج الألعاب - الوسط المائي - الانتقال والتركيز - الأطفال المصابين بالفرط الحركي